Effects of Metal Sulfate Electrolyte Additives on Charge Acceptance in Agm Batteries - (:unkn) unknown (My University, 2018)
In the United States the transportation sector is the second largest source of greenhouse gas emissions, making up 27% of the total greenhouse gas emitted in 2015. Within the transportation sector passenger vehicles make up the largest percentage of emissions at 41.6% [1]. To help curb passenger vehicle CO2 emissions manufacturers are adopting increasing amounts of hybrid technology. Micro-hybrid technology utilizes a typical internal combustion engine and lead-acid battery partnered with Start-Stop technology and regenerative breaking to decrease emissions by 5-12%. To keep up with the electrical demands of this type of use, advanced lead acid batteries in the form of Absorbent Glass Matt (AGM) batteries are being used in these systems. With an ever-growing electrical demand placed on these batteries, improvements to the charge acceptance of these batteries is required. Much research is being done on adding carbon materials to the batteries lead plates and various compounds to the electrolyte to increase charge acceptance. For the original experiments contained in this paper, the use of metal ion sulfate salts to improve charge acceptance is investigated. Results establish that different metal ions and different concentrations of ions have a broad range of effects on charge acceptance. Magnesium, zinc, and aluminum ions showed a 32-41% increase in charge acceptance at a 60% state of charge.
Keywords: Additive; Battery; Electrolyte; Lead-Acid